Memristive Devices for Quantum Metrology. Issue 5 (13th April 2020) - Milano, Gianluca; Ferrarese Lupi, Federico; Fretto, Matteo; Ricciardi, Carlo; De Leo, Natascia; Boarino, Luca
Abstract: As a consequence of the redefinition of the International System of Units (SI), where units are defined in terms of fundamental physical constants, memristive devices represent a promising platform for quantum metrology. Coupling ionics with electronics, memristive devices can exhibit conductance levels quantized in multiples of the fundamental quantum of conductance G 0 = 2 e 2 / h . Since the fundamental quantum of conductance G 0 is related only to physical constants that assume fixed value in the revised SI, memristive devices can be exploited for the practical realization of a quantum‐based resistance standard that, differently from quantum‐Hall based devices conventionally adopted as resistance standards, can operate in different ambient conditions (air, vacuum, harsh environment), in a wide range of temperatures and without the need of an applied magnetic field. In this work, the possibility of using memristive devices for quantum metrology is critically discussed, based on recent experimental and theoretical advances on quantum conductance phenomena reported in literature. Thanks to the high operational speed, high scalability down to the nanometer scale, and CMOS compatibility, memristive devices allow on‐chip implementation of a resistance standard required for the realization of self‐calibrating electrical systems and equipment with zero‐chain traceability in accordance with the revised SI. Abstract : Memristive devices exhibiting quantum conductance levels are proposed as quantum metrology devices in the light of the redefinition of the International System of Units. Due to their high scalability and compatibility with CMOS technology, memristive devices working in air at room temperature represent promising platforms for on‐chip embedding of a resistance standard for realizing self‐calibrating systems with zero‐chain traceability.